Reawakening the ‘Dish with One Spoon’: The Haudenosaunee and Michi Saagiig Economies of Southern Ontario Past, Present and Future - Barberstock, Ryan E. (2023)
In this thesis, we explore the significance of the Dish with One Spoon, a Wampum Belt treaty that embodies a profound First Nations connection rooted in both cultural ties and economic interests. This treaty plays a pivotal role in shaping the development of an enduring economic reality between the Haudenosaunee and the Michi Saagiig Nishnaabeg Peoples. Furthermore, this research focuses on the nation-to-nation resource-sharing agreement for the common lands of Southern Ontario among First Nations treaty holders, offering an examination of various facets and capabilities of the Dish with One Spoon from an economic standpoint. Despite the impacts of colonization, its resilience and sovereignty have endured, encompassing a significant portion of Southern Ontario which is protected by Wampum Belt diplomacy. The Dish with One Spoon treaty constitutes a multinational Indigenous economic accord, integrating perspectives from the land and waters. Beyond establishing rights and privileges, the Dish with One Spoon recognizes First Nations Peoples, plant life, and animals as active participants and decision-makers in the economic self-determination of their shared treaty territory. Framed as theory and informed by the Two-Row method, this research demonstrates how the Dish with One Spoon presents a distinctive model of Indigenous regional economics. This model places a premium on the economic autonomy of First Nations and their interdependent relationship with the local ecology. Moreover, it underscores the importance of acknowledging the agency and autonomy of the land in making treaty-based economic decisions, recognizing its crucial role in resource conservation and its intrinsic link to economic development. PhD